microRNA level is raised in the hair shafts of patients with dematomyositis in comparison with normal subjects and patients with scleroderma - Inoue, Minami; Jinnin, Masatoshi; Wang, Zhongzhi; Nakamura, Kayo; Inoue, Kuniko; Ichihara, Asako; Moriya, Chikako; Sakai, Keisuke; Fukushima, Satoshi; Ihn, Hironobu (International journal of dermatology, 2016)
Background The diagnosis of dermatomyositis is sometimes difficult. We tried to evaluate the possibility that levels of Homo sapiens microRNA‐214 (hsa‐miR‐214) in hair roots or hair shafts can be a useful marker of the disease. Methods A single hair root and five pieces of hair shafts were obtained from nine patients with dermatomyositis, 15 normal subjects, and 18 patients with scleroderma before treatment. RNAs were purified from the hair roots and hair shafts using commercially available kits. cDNA was synthesized from the RNA, and miR‐214 levels were measured with quantitative real‐time polymerase chain reaction. Receiver operating characteristic curve analysis was performed to evaluate the diagnostic performance of hair microRNA levels. Results The levels of miR‐214 in hair shafts of patients with dermatomyositis were significantly higher than those of normal subjects and patients with scleroderma. By receiver operator curve analysis of hair shaft miR‐214 levels to distinguish patients with dermatomyositis from normal subjects, the area under the curve was 0.90. The duration between symptom onset and the first visit to the hospital was significantly shorter in patients with elevated hair shafts miR‐214 levels, suggesting that they have more severe subjective symptoms. On the other hand, we could not find significant differences in hair root miR‐214 levels among normal subjects and patients with dermatomyositis and scleroderma. Conclusions Hair shaft miR‐214 levels are useful for diagnosis and evaluating the disease severity of dermatomyositis. Hair microRNA levels may have potential to be a novel and less invasive biomarker.